2011
DOI: 10.1590/s0102-77862011000100007
|View full text |Cite
|
Sign up to set email alerts
|

Estudo de caso de uma situação atmosférica entre 12 e 19 de setembro de 2008, com algumas características semelhantes ao evento Catarina

Abstract: RESUMOEste trabalho apresenta uma análise das condições sinótica e dinâmica associadas ao desenvolvimento do ciclone ocorrido entre 12 e 19 de setembro de 2008, com o objetivo de destacar diferenças e semelhanças com o ambiente em que se inseriu o evento Catarina em março de 2004. As principais semelhanças foram encontradas no padrão sinótico geral: a ocorrência de um padrão típico de bloqueio do tipo dipolo associado à anomalia de vorticidade potencial em altos níveis; cavado em níveis médios com inclinação p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…The attention of researchers and weather forecasters to the genesis of subtropical cyclones over the southwestern South Atlantic Ocean (SAO) was attracted with the occurrence of the first documented hurricane in March 2004 [14][15][16], called hurricane Catarina, once this system resulted from a tropical transition (an extratropical disturbance evolved to subtropical and after to a tropical cyclone). Until Catarina, little or no attention was given to the tropical development over the SAO due to unfavorable environmental conditions for tropical systems, i.e., the necessity of a sea surface temperature (SST) warmer than 26.5 • C and a weak vertical wind shear (lower than 8 m•s −1 between the 200 and 850 hPa vector winds) [7,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The attention of researchers and weather forecasters to the genesis of subtropical cyclones over the southwestern South Atlantic Ocean (SAO) was attracted with the occurrence of the first documented hurricane in March 2004 [14][15][16], called hurricane Catarina, once this system resulted from a tropical transition (an extratropical disturbance evolved to subtropical and after to a tropical cyclone). Until Catarina, little or no attention was given to the tropical development over the SAO due to unfavorable environmental conditions for tropical systems, i.e., the necessity of a sea surface temperature (SST) warmer than 26.5 • C and a weak vertical wind shear (lower than 8 m•s −1 between the 200 and 850 hPa vector winds) [7,15].…”
Section: Introductionmentioning
confidence: 99%
“…After Catarina, the first subtropical cyclone over the SAO that received a name was Anita, occurring in March 2010 [3,11,17,18]. References [11][12][13][14][15][16][17] studied the lifecycle of Anita and documented the presence of a dipole-blocking pattern at mid-upper levels, which provided weak vertical wind shear and, consequently, adequate conditions for the cyclone intensification. Moreover, Reference [11] suggested that Anita did not transition to a tropical cyclone near the Brazilian coast because its semi-stationary behavior contributed to both rainfall and the mix of the upper level layer of ocean that helped weaken the sea-air turbulent heat fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…Com relação à América do Sul, eventos de seca na Amazônia foram registrados em 1997em /1998em , 2005em e 2010em (MARENGO et al, 2008em , 2011 e, no sudeste do Brasil, em 2001 e 2014 (COELHO ET AL., 2015). Em 2004, a costa sul do Brasil foi afetada pelo primeiro furacão documentado no oceano Atlântico Sul, o Catarina (McTAGGART-COWAN et al, 2005;IWABE et al, 2011). Os eventos extremos afetam diretamente a disponibilidade hídrica, o setor energético, a agricultura entre outros.…”
Section: Introductionunclassified
“…Global and hemispheric scale studies have shown cyclone spatial distributions but generally, do not allow a detailed focus on the regional features of cyclones and the storm tracks. Some studies concerning cyclones and their evolution have focused on the South Atlantic, but have usually been restricted to South America Rao, 1991, 1994;Mendes et al, 2010;Vera et al, 2002;Reboita et al, 2010a) or individual case studies (Seluchi and Saulo, 1998;Funatsu et al, 2004;Piva et al, 2008Piva et al, , 2010Piva et al, , 2011Iwabe et al, 2011;Dias Pinto and Da Rocha, 2011;Dias Pinto et al, 2013;Gozzo and da Rocha, 2013;Dutra et al, 2017). These studies provide insights into the development of cyclones in South America but do not provide a climatological view of the forcing mechanisms acting on cyclones over the South Atlantic Ocean.…”
mentioning
confidence: 99%